PERBANDINGAN PIDANA DENDA DALAM DUA REZIM KUHP INDONESIA - Bambang Antariksa (Journal Recht (JR), 2024)
The fine as one of the penalties in Indonesian criminal law, has been applied since the enactment of the Wetboek von Strafrecht (Dutch Penal Code). The enactment of Law Number 1 of 1946 concerning the Regulation of the Criminal Law which is the transplantation of law the Dutch Penal Code into a Indonesia criminal law, until enactment of Law Number 1 of 2023 concerning the Criminal Code (National Penal Code), the existence of fines as one of the forms of sentencing, was maintained. However, there are a number of differences regarding the formulation of fines between two regimes of Indonesia Penal Code. This paper aims to compare the scope of fines formulated in the two regimes of the Indonesian Penal Code. This research uses normative legal research methods or doctrinal legal research. This research is a micro-law comparative research, which is to compare certain parts of the law related to the object of the problem, namely the comparison of the scope of fines formulated between the National Criminal Code and the Old Penal Code. The results of the study revealed that there are similarities and differences in the scope of fines formulated, between two regimes of Indonesia Penal Code. The similarity is that fines are one type of sentencing still exist, both in the National Penal Code and the Old Penal Code. The difference is, the National Penal Code regulates several provisions regarding fines which in the Old Penal Code were not regulated, such as: the classification of fines into eight categories, the period and method of payment of fines, provisions regarding confiscation and auction of property/objects of convicts who do not pay fines, penalties in lieu of fines which were previously in the form of confinement into imprisonment, supervision, and community service. In addition, affirming fines as the main punishment for corporation, regulating the implementation of various types of imperative-cumulative and imperative-facultative penalties, namely fines with other punishment, and finally is order to change the provisions of confinement stipulated all of local regulations to be replaced by fines.